2014
DOI: 10.1039/c3ay42031k
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating HPLC-DAD method for the simultaneous determination of fluoroquinolones and corticosteroids in ophthalmic formulations

Abstract: We develop and validate a stability-indicating assay method for simultaneous determination of gatifloxacin and prednisolone acetate, or of ciprofloxacin hydrochloride and dexamethasone in combination and in the presence of degradation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The factors (chromatographic conditions) selected to examine the robustness were the flow rate, percentage of acetonitrile, and pH of the water in the mobile phase. Each factor was investigated at three levels (-1, 0, and + 1) (Sversut et al, 2014). Level 0 refers to the normal chromatographic conditions, i.e., the conditions employed in the proposed method.…”
Section: Robustnessmentioning
confidence: 99%
“…The factors (chromatographic conditions) selected to examine the robustness were the flow rate, percentage of acetonitrile, and pH of the water in the mobile phase. Each factor was investigated at three levels (-1, 0, and + 1) (Sversut et al, 2014). Level 0 refers to the normal chromatographic conditions, i.e., the conditions employed in the proposed method.…”
Section: Robustnessmentioning
confidence: 99%
“…Various methods have been reported describing the assay of the fluoroquinolones and corticosteroids either singly or in combination. These methods include spectrophotometry (Abdel‐Razeq, Darwish, Zaazaa, Nasr, & Zeinab, 2015; Patel & Patel, 2013; Pradhan, Raiyani, Shah, Patel, & Upadhyay, 2015; Sversut et al, 2017), HPLC (El Gammal, El‐Wasseef, El‐Ashry, & Saadia, 2018; Gandhi, Rao, & Rao, 2016; Saad, Essam, Elzanfaly, & Amer, 2020; Sher, Fatima, Perveen, & Siddiqui, 2019; Sversut et al, 2014), thin‐layer chromatography (TLC) (Dorofeev, Konovalov, Kochin, & Arzamastsev, 2004; Musharraf, Fatima, & Sultana, 2012; Saad et al, 2020; Seid, Hymete, & Bekhit, 2012), capillary electrophoresis (Al Azzam, Saad, Adnan, & Aboul‐Enein, 2010; Alnajjar, 2013; Bourdon et al, 2013; Gallego & Arroyo, 2003; Horstkötter & Blaschke, 2001; Maher et al, 2013; Olędzka, Kowalski, Plenis, & Bączek, 2017; British Pharmacopoeia, 2013; Song, Bai, Jia, & Zhou, 2008; Suliman, Elbashir, & Schmitz, 2015; Wang et al, 2009; Zhu, Jiang, & Hu, 2002) and electrochemical methods (El‐Rahman, Lotfy, Hegazy, Rezk, & Rostom, 2015; Smajdor, Piech, & Paczosa‐Bator, 2016; Zhang, Gu, Ding, Li, & Liu, 2013; Zhang, Gu, Ding, Zhang, & Li, 2013). After a thorough investigation of literature, it was observed that no capillary electrophoretic method has been published for the simultaneous assay of the four chosen drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar methods have been used for determination of some group of fluoroquinolones in tilapia samples [5] , in eggs [6] , in milk [7] and in sheep plasma [8] as veterinary drug residues. The HPLC was used also for investigation of some fluoroquinolones in pharmaceutical preparations [9][10][11][12] . These methods have been reported for determination of the fluoroquinolones individually [9] or in different combinations [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC was used also for investigation of some fluoroquinolones in pharmaceutical preparations [9][10][11][12] . These methods have been reported for determination of the fluoroquinolones individually [9] or in different combinations [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%